2021
DOI: 10.3390/s21134360
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Response According to the Greenness Index of Subway Station Space

Abstract: This study proposed a plan for implementing a pleasant and healthy indoor landscape in subway station space. To this end, it established a 3D landscape model of the subway interior by reviewing previous studies on indoor landscape and the greenness index of indoor spaces. Moreover, it investigated and analyzed psychophysiological responses of users to environmental indoor landscape design in subway station space. Subway stations were classified as underground subway stations and ground subway stations accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…There was likely a higher effect of interior landscapes in these places. Kim and Lee [40] found that there were different preferences for green space rates in underground and above-ground spaces with light in subway stations. GI preference characteristics based on the presence and size of windows in residential spaces should be examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There was likely a higher effect of interior landscapes in these places. Kim and Lee [40] found that there were different preferences for green space rates in underground and above-ground spaces with light in subway stations. GI preference characteristics based on the presence and size of windows in residential spaces should be examined in the future.…”
Section: Discussionmentioning
confidence: 99%